(untitled) (Medicine Today, 2017)
It was across sectional study to explore the factors responsible for Acne among the undergraduate medical students in Z.H. Sikder Women’s Medical College, Dhaka. In this study, it revealed that 34,38% of respondents were suffering from acne where habit of smoking (32%) , using of cosmetics (36%), taking of fast food (82%) & taking of less water (36%) & premenstrual flare up (66%) are responsible for aggravating & influencing factors for acne. This study further shown that majority (83.63%) of the respondents are suffering from acne in face, 58.18% in pimple stage, 60.00% in grade IV & 38.18% in grade III. BMI has no influence for the causation of acne as it occurs most (66.45%) in the group where BMI is within normal range from 20-24. Among the respondents, scar present in 36% & hyper pigmentation in 24% as they did not maintain personal hygiene properly. Medicine Today 2017 Vol.29(2): 30-32